2010
DOI: 10.1007/s00403-010-1059-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of melanogenesis inhibition by propafenone

Abstract: Melanogenesis is a physiological process that results in the synthesis of melanin pigments, which play a crucial protective role against skin photocarcinogenesis. The present study was conducted to determine the inhibitory effects of propafenone on melanogenesis and to elucidate the molecular events involved in the inhibition of melanogenesis by propafenone. To accomplish this, several experiments were conducted using human epidermal melanocyte cells. The melanin content and cAMP production were evaluated, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…A recent study reported that degradation of MITF is related to the suppression of the α-MSH-induced cAMP-dependent melanogenic pathway in melanoma cells [27]. Consequently, we theorized that gallic acid-induced MITF down-regulation is also involved in the cAMP signal transduction cascade.…”
Section: Discussionmentioning
confidence: 88%
“…A recent study reported that degradation of MITF is related to the suppression of the α-MSH-induced cAMP-dependent melanogenic pathway in melanoma cells [27]. Consequently, we theorized that gallic acid-induced MITF down-regulation is also involved in the cAMP signal transduction cascade.…”
Section: Discussionmentioning
confidence: 88%
“…To better understand the molecular mechanisms of Reinduced inhibitory effect, we further examined the effect of Re on the mRNA expression level of melanogenic transcription genes. It has been reported that MITF down-regulation is related to the suppression of the cyclic AMP-dependent signaling pathway stimulated by α-MSH in melanoma cells (Huh et al, 2010). However, in the current study, we did not evaluate the inhibitory activity of ginsenoside Re in the cyclic AMP-mediated melanin production.…”
Section: Discussionmentioning
confidence: 39%
“…It has recently been reported that MITF degradation is related to suppression of the cAMP-dependent melanogenic pathway stimulated by ␣-MSH in melanoma cells (Kim et al, 2008;Huh et al, 2010). Therefore, we hypothesized that PPNC-induced MITF down-regulation is involved in the cAMP signal transduction cascade.…”
Section: Discussionmentioning
confidence: 92%